Pengaruh Net Ekspor dan Kebijakan Fiskal Terhadap Kebijakan Hutang Pemerintah di Indonesia - Silfi Elia; Mike Triani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This research  aims to determine (1) the effect of net export on government debt in Indonesia, (2) the effect of fiscal policy on government debt in Indonesia, (3) the effect of net export and fiscal policy on government debt in Indonesia. The method used in this study is multiple linear regression. The research type is descriptive research while the data used is time series data from 1987-2016 obtained from documentation of Bank Indonesia, and BPS Indonesia. The results of this study indicate that (1) net export has a significant positive effect on government debt in Indonesia (2) fiscal policy has a significant positive effect on government debt in Indonesia (3) net export and fiscal policy has a significant positif effect on government debt in Indonesia. Based on this research is expected to provide information about government debt as well as the factors that influence, and so the government and society can monitor and increase efforts to reduce government debt.